Partisipasi guru smp terhadap penerapan kawasan tanpa rokok: studi komparasi di Kabupaten Sleman dan Kulonprogo - Arie Kurniardi; Yayi Suryo Prabandari (Berita Kedokteran Masyarakat (BKM), 2017)
PurposeThis study aimed to explore the difference of participation in non-smoking areas implementation among junior high school teachers in Kulon Progo and Sleman.MethodThis research used a cross-sectional study design. The samples in this study were the junior high school teachers from Kulon Progo and Sleman District. The analysis used independent sample t-tests.Results There was no significant difference in knowledge level, self-efficacy, smoking status and school policy in Kulon Progo and Sleman districts. There was a difference in accessibility level of information about smoking ban and teacher participation to implement non-smoking areas in Kulon Progo and Sleman.Conclusion The most dominant factor that influenced the participation of junior high school teachers towards the implementation of nonsmoking areas in Kulon Progo Regency and in Sleman District of Yogyakarta is the accessibility of information about smoking ban.